Determination of thermal sensation on transient conditions - Dahlan, Nur Dalilah; Gital, Yakubu Y.; Hussein, Mohd Kher (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The objective of this study is to investigate the difference in thermal environment and human response between air-conditioned closed space and a semi-open space. The thermal response of the subjects in transitional space as they experienced step changes in temperature when moving from outdoor environment to indoor air-conditioned and back to outdoor was examined. The thermal sensation was investigated using a questionnaire and a comprehensive package of micro-metrological instruments. Experiment was conducted to examine the immediate thermal sensation of the subjects when walking from one set of thermal condition to another. Subjects were exposed to three different environmental conditions for 5 to 20 minutes (semi-outdoor, indoor and semi-outdoor). Skin temperature, subjective thermal sensation and comfort were recorded throughout the experiment. Results showed that there is variation in skin temperature as observed in sensation scores between the sequences. The predicted mean vote overshoot all through the sequence as the subjects move from one location to another. Since PMV is widely used as a tool to predict thermal comfort in steady-state environment, it may not be applied to predict thermal sensation in a transient environment. The result of this study can help to improve the PMV model to be applied in a transient environment. This outcome would be suitable in circumstances such as movement in a lobby which is semi-outdoor to predict thermal sensation.